ANALISIS TINGKAT KESEJAHTERAAN MASYARAKAT NELAYAN DI DESA BARA: (Analysis of Welfare Level of Fishermen Community) - Fesanrey, Wilda; Tuhulola, Eva (Uniqbu Journal of Exact Sciences, 2022)
This study aims to determine the level of welfare of the fishing community in Bara Village, Airbuaya District, Buru Regency. Methods This research uses a survey method, with interview techniques using a questionnaire (a list of questions). The sampling method in this study was carried out using purposive sampling, namely the technique of determining the sample with certain considerations. Respondents taken in this study amounted to 18 people or 30% of the total population of 60 fishermen. Community welfare is basically to fulfill the feasibility of community life, where community members have the desire to fulfill the needs of their family life. The welfare of the community is also part of the assessment of the quality of life, the quality of life in question is people who are far from low socio-economic conditions. The welfare of respondent fishermen in Bara Village, Airbuaya District is considered prosperous because if it is seen from the Fisherman's Exchange Rate (NTN) of fishermen's households in Bara Village, which is 56,264,125 with an INTN value equal to 1, this means that the fishermen's family is only able to meet their needs. the subsystem.